An imaging pill for gastrointestinal endoscopy. - Panescu, D.
This paper discusses on a miniaturized device that greatly reduces the discomfort experienced by the patient during gastrointestinal (GI) endoscopy. The device carries a miniaturized video camera, is equipped with a tracking device, and is the size of a pill, thereby making it easy to swallow. While this imaging pill is moved through the GI tract by the natural action of the intestinal muscles, it transmits images to a recorder carried on a belt worn by the patient. Thus, offering a more accurate imaging of most regions of the GI tract. In 2001, Given Imaging Ltd., the developer of the device, convinced the U.S. Food and Drug Administration (FDA) to approve this revolutionary technology for clinical use.
Keywords: Given Imaging Ltd; Gastrointestinal endoscopy; Imaging pill; Intestinal muscles; Miniaturized device; Miniaturized video camera; Tracking device